UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI PELUANG KELAS XI SMA NEGERI 21 MEDAN - Indriyani Indriyani; Suwanto Suwanto (Mahesa Research Center, 2020)
This research is a classroom action research, which aims to look at students' mathematical problem-solving abilities and student mathematics learning outcomes by applying the Contextual Teaching and Learning model in class XI IPA-1 SMA Negeri 21 Medan. The research subjects were 35 students. At the beginning of the study, observations were made to find out the weaknesses of students and the problems faced when teaching and learning activities took place. In addition to the data of mathematical problem-solving abilities that were analyzed, student learning activities were also analyzed. Based on the research results obtained observations in the first cycle; writing/reading (35.67%), working on student worksheets (23.33%), asking fellow friends (22%), asking teachers (12.33%), and activities not relevant to teaching and learning activities (6.67%). In the second cycle obtained writing/reading (28.3%), working on student worksheets (28%), asking fellow friends (24%), asking teachers (18.7%), and activities not relevant to teaching and learning activities (1%). The results for classical completeness obtained in the first cycle of 62.9%, but in the second cycle of 85.7%.